Evidence for a nonmonotonic relationship between ecosystem‐scale peatland methane emissions and water table depth. Issue 5 (13th May 2014) - Brown, Mathew G.; Humphreys, Elyn R.; Moore, Tim R.; Roulet, Nigel T.; Lafleur, Peter M.
Abstract Although temporal and spatial variations in peatland methane (CH4) emissions at broad scales are often related to water table (WT) using a linear relationship, a potentially complex relationship exists between these variables locally and over shorter time scales. To explore this issue, CH4 fluxes were measured using eddy covariance at the Mer Bleue bog over two summer seasons. Peak CH4 emissions (30 to 50 mg CH4‐C m−2 d−1) occurred not when the WT was closest to the surface but instead, when it dropped to 40 to 55 cm below the surface. When the WT was below or above this zone, average fluxes were ~14 mg CH4‐C m−2 d−1. We speculate this critical zone coincides with the necessary redox potentials and sources of fresh organic material that lead to maximum production of CH4 and/or with conditions that lead to degassing of stored CH4. However, as expected, total summer CH4 emissions were 47% lower during the drier year. This occurred in part because the WT was within the critical zone for fewer days in the drier year but also because after an extended midsummer dry period there was little recovery of CH4 emissions, even a month after rewetting.